Pengujian Black Box pada Aplikasi Perpustakaan Berbasis Web Menggunakan Teknik Equivalence Partitioning - Deny Setiawan; Muhammad Ardiansyah Fadhillah; Anggun Wibawa; Irwan Sugiarto; Agus Mulyana; Irpan Kusyadi (Program Studi Teknik Informatika Universitas Pamulang, 2020)
In determining the level of quality of a software it is necessary to test the software. Tests tested can include specifications, design, and coding of the software. This test is conducted to test web-based library software. This test uses the Black Box Testing method using the Equivalence Partitioning technique. Black Box Testing is applied in order to find errors in software related to erroneous functions, errors in interface display, data structure errors or access rights in external databases, sub-optimal performance in a process, and errors in initialization or termination. The Equivalence Partitioning technique defines the cases to be tested by finding some errors and minimizing the number of cases that must be made. The Equivalence Partitioning test case design is based on the premise of the input and output of a component which is partitioned into classes according to the specifications of that component, which are treated equally (equivalence). It can also be assumed that the results of an input produce the same response. The expected result of testing this software is to ensure that this software is free from errors so that in its use there will be no obstacles that prevent the user from doing his work. And inform that the software is in accordance with predetermined specifications.